Menghapus Jejak Kebijakan Masa Lalu: Perubahan Kebijakan AS terkait Isu pencurian Kekayaan Intelektual melalui Media Siber oleh Tiongkok - Hafrian Yusuf Ramdhani; Mohamad Rosyidin (Journal of International Relations Diponegoro, 2019)
This research aims to find out the reason why Donald Trump alter US approach regarding to China Cyber IP theft. Initially, US under Obama administration has reached an agreement on Cyber security issues. Both countries agreed to not conduct or support IP theft through internet. However, as Donald Trump assume Presidency, he prefer imposing tariff on China product due to China Cyber IP theft activity.in analyzing the case this research employ the concept Operational Code by Alexander George. According to George, actor needs beliefs to understand the world and selecting the best means to achieve his ends. This research will apply literature study for data collection and content analysis for data analysis. The main argument of this research is Donald Trump’s rivalry oriented Philosophical beliefs and aggressive instrumental beliefs as the main cause the tariff imposition